2019
DOI: 10.1177/0363546519871896
|View full text |Cite
|
Sign up to set email alerts
|

Management of the Failed Latarjet Procedure: Outcomes of Revision Surgery With Fresh Distal Tibial Allograft

Abstract: Background: Patients with recurrent anterior glenohumeral instability after a failed Latarjet procedure remain a challenge to address. Complications related to this procedure include large amounts of bone loss, bone resorption, and issues with retained hardware that necessitate the need for revision surgery. Purpose: To determine the outcomes of patients who underwent revision surgery for a recurrent shoulder instability after a failed Latarjet procedure with fresh distal tibial allograft. Study Design: Case s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
51
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 37 publications
1
51
0
Order By: Relevance
“…‖ Sources of autograft include iliac crest bone graft (ICBG), ¶ distal clavicle, 92 and free partial-thickness coracoid (leaving the conjoint tendon attached to the remaining anatomic coracoid and not transferred with the graft as performed during a Latarjet/Bristow procedure). 7,95 Sources of allograft include the distal tibia, 40,73,75 proximal tibia, 87 distal femur, 87 iliac crest, 2,90,108 and femoral head. 98 The use of autografts may be associated with donor site morbidity, including risk for infection, hematoma, sensory disturbances, and an additional scar.…”
mentioning
confidence: 99%
“…‖ Sources of autograft include iliac crest bone graft (ICBG), ¶ distal clavicle, 92 and free partial-thickness coracoid (leaving the conjoint tendon attached to the remaining anatomic coracoid and not transferred with the graft as performed during a Latarjet/Bristow procedure). 7,95 Sources of allograft include the distal tibia, 40,73,75 proximal tibia, 87 distal femur, 87 iliac crest, 2,90,108 and femoral head. 98 The use of autografts may be associated with donor site morbidity, including risk for infection, hematoma, sensory disturbances, and an additional scar.…”
mentioning
confidence: 99%
“…Similarly, the Latarjet for glenoid bone loss and remplissage procedure for humeral head bone loss have been reported with success in the adolescent population [14, 30•]. Additionally, the use of Iliac crest and distal tibia allograft have been described in adult populations for the treatment of glenoid bone loss, but never in children [35,40]. Distal clavicle autograft has also been utilized in adults for glenoid bone loss; however, the open distal clavicular physes would likely make this undesirable in adolescent patients [41].…”
Section: Outcomes Of Revision Surgerymentioning
confidence: 99%
“…It’s not surprising that such a process should occur; other glenoid bone grafts have been shown to remodel, most commonly down to the original glenoid contour. 16,25 As screws are often used to fix the coracoid in place, a theoretical consequence of excessive absorption is exposure of the screws 18 and subsequent pain or secondary injury. 8 Graft absorption may be more likely when the Latarjet is used in shoulders with little to no glenoid bone loss.…”
mentioning
confidence: 99%
“…A subsequent comparative study by many of the same authors found 65.1% mean resorption in patients who had no glenoid deficiency, compared with 39.6% among those with more than 15% glenoid bone loss. 6 A recent study of revisions of failed Latarjet procedures by Provencher and colleagues 18 found that a mean 78% of the graft bone had resorbed, raising the possibility that this resorption may in some cases increase the risk of recurrent instability.…”
mentioning
confidence: 99%
See 1 more Smart Citation